The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s00415-020-09825-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal surface autoantibodies in dementia: a systematic review and meta-analysis

Abstract: Introduction Neuronal antibodies can cause encephalopathy syndromes often presenting with subacute cognitive impairment, sometimes resembling neurodegenerative dementias. Methods We searched Medline and Embase for studies reporting associations between neuronal surface antibodies in allcause dementia versus controls. Random-effects meta-analysis was used to pool adjusted estimates across studies. Results Six studies were included, all reporting frequency of serum NMDAR antibodies in dementia with four also rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…In a recent meta-analysis, we reported that both IgG and IgA/M serum NMDAR antibodies were more prevalent in atypical dementias vs healthy controls, while there was no difference for all-cause dementia. However, the total number of studies was small and “atypicality” was inconsistently defined and in some studies may have been done so post-hoc, necessitating caution in interpretation of this intriguing result 129 .…”
Section: Gaba a R Encephalitismentioning
confidence: 99%
“…In a recent meta-analysis, we reported that both IgG and IgA/M serum NMDAR antibodies were more prevalent in atypical dementias vs healthy controls, while there was no difference for all-cause dementia. However, the total number of studies was small and “atypicality” was inconsistently defined and in some studies may have been done so post-hoc, necessitating caution in interpretation of this intriguing result 129 .…”
Section: Gaba a R Encephalitismentioning
confidence: 99%
“…Autoantibody-based clinical neurological and psychiatric syndromes are a rapidly growing field in clinical neuropsychiatry and geriatric psychiatry as they often present with cognitive decline as the first or concomitant symptoms (Gibson et al 2020;Bartels et al 2019;Arino et al 2016;Loane et al 2019;Sechi and Flanagan 2019). A recent study focusing on the increasing frequency of N-methyl-d-aspartate receptor antibodies (NMDAR)-mediated atypical dementia (Gibson et al 2020). In this context, atypical dementia entailing an early-onset and atypical presentation is more often reported to be associated with NMDAR autoantibodies (Gibson et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study focusing on the increasing frequency of N-methyl-d-aspartate receptor antibodies (NMDAR)-mediated atypical dementia (Gibson et al 2020). In this context, atypical dementia entailing an early-onset and atypical presentation is more often reported to be associated with NMDAR autoantibodies (Gibson et al 2020). Individual specific autoantibodies such as α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) subunit ionotropic glutamate receptor 3 (GluA3) autoantibodies (Palese et al 2020) or contactin-associated protein-like 2 (CASPR2) autoantibodies (Guo et al 2020) have been demonstrated in homogeneous groups of patients with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…We thoroughly discuss the potential role of KCNA2 in both cases and provide recommendations for future investigations. We emphasize the importance of taking a systematic diagnostic approach in patients presenting with clinical features signaling an autoimmune-related cognitive decline that they might mimic, but must be differentiated from neurodegenerative diseases, as the therapeutic implications are immense and a delay in inducing effective immunotherapy will compromise the patient’s clinical outcome [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%